97.5k views
3 votes
Solve the system using elimination and describe your steps.

3x + y = 9
5x + 4y = 22
-------------------

2 Answers

4 votes

Answer:

x = 2, y = 3

Explanation:

3x + y = 9 (1)

5x + 4y = 22 (2)

Multiply equation (1) by -4 and add to equation (2)

-12x - 4y = -36

5x + 4y = 22

-7x = -14

x = 2

Using any equation, solve for y

5(2) + 4y = 22

4y = 12

y = 3

User Kwon
by
4.9k points
2 votes

Answer:

x = 2, y=3

Explanation:

3x + y = 9

5x + 4y = 22

Multiply the first equation by -4

-4(3x + y) = 9*-4

-12x -4y = -36

Add this to the second equation to eliminate y

-12x -4y = -36

5x + 4y = 22

---------------------------

-7x = -14

Divide each side by -7

-7x/-7 = -14/-7

x = 2

Now find y

3x+y = 9

3(2) +y = 9

6+y = 9

Subtract 6 from each side

-6+6 +y = 9-6

y = 3

User Ezgar
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.